Discovering Pope Francis : the roots of Jorge Mario Bergoglio's thinking - Lee, Brian Yong; Knoebel, Thomas L. (Collegeville : Liturgical Press, 2019)
"A collection of essays designed to promote theological understanding by contextualizing the thought of Pope Francis--from his understanding of history to his theology of mission--within important theological conversations rarely heard in the US Catholic Church"--
Includes bibliographical references (pages 215-236) and index.
Keywords: Francis, -- Pope, -- 1936-